High temperature and wide range 40-GHz passive modelocking operation of an AlGaInAs 1.55-µm strained quantum well laser - Hou, L.; Stolarz, P.; Ironside, Charlie; Sorel, M.; Bryce, C. (2008)
Passive mode locking at 40GHz is reported on AlGaInAs strained multi-quantum-well lasers. The devices show very stable mode locking operation over a very large range of biasing conditions and up to temperatures of 100°C. ©2008 IEEE.